Investigation of the change in the strength properties of a soil mass by mechanical sensing - Zaichenko, Stefan; Frolov, Oleksandr; Stovpnyk, Stanislav; Veremiichuk, Yurii (Eastern-European Journal of Enterprise Technologies, 2018)
Determination of depth distribution of strength characteristics and comparison with analytically determined values allows obtaining data on the depth of various morphological horizons, the presence of voids and inclusions. The sensing process occurs due to soil strengthening, which was considered in the analysis of changes in the penetration force. The present stage of development of means for determining the soil properties is characterized by the application of mechatronic systems, which allow obtaining data with high accuracy, reliability and performance. In order to develop the experimental sample, the basic approaches to the creation of a geomechatronic complex for surface soil monitoring, which determine the main objectives, application scope, quality criteria were developed. The presence of geotechnical deviations in the soil mass is accompanied by changes in the penetration force, which was proposed to be measured by a strain gauge dynamometer with the recording of the rod penetration depth. The program algorithm used is a cyclic structure in which the data are logically recorded from the force sensor and the step of the rod, which determines its position. The implementation of the developed algorithm allows determining penetration forces and changes in the strength parameters of the soil mass with high accuracy (0.05 %), which makes it possible, by comparing with the analytically determined distribution, to reveal the position of geoanomalies.